Size, Technology, Environment and the Structure of Organizations - Ford, Jeffrey D.; Slocum, John W. (Academy of Management Review, 1977)
Literature pertaining to the structural influence of size, technology, and environment is reviewed. Results indicate similar structural predictions are offered by each of the three contingency variables. The roles of measurement, unit and level of analysis, variable and effect independence, and variable dominance in research inconsistencies and future research directions are considered.